The muscles` relaxation characteristics improvement of belt wrestlers using exercises on the basis of the instantaneous simulators - Valinurov, R.; Denisenko, Y.; Akhmetov, A.; Gilmutdinov, I.; Seliverstova, N. (BIO Web of Conferences, 2020)
In modern times, qualified athletes reached high level of physical fitness. That`s why, the greater increase in the volume and intensity of the training process becomes difficult task. The first step is to develop the search for new forms of the training process organization. They create optimal conditions for the full-value realization of the adaptive possibilities and the restoration of energy resources. Therefore, it is very important to search for fundamentally new means and methods to improve the physical performance of athletes. One of them is often power simulators, in which the resistance force is formed by a set of brakes that have significant inertia. However, special research and experience in sports practice indicate that the use of traditional strength training equipment, although it contributes to the development of strength quality. At the same time negatively affects the development of speed and endurance. The problem of finding new tools that cannot slow down the development of speed and endurance during the development of strength qualities remains urgent. Among the few tools of this kind, special attention should be paid to exercises that help improve the relaxation characteristics of the muscles. A number of studies showed the beneficial effect of special exercises that improve the relaxation characteristics (relaxation rate) of skeletal muscles, and contribute to improving the effectiveness of special physical performance and improving sports results.